1998
DOI: 10.1046/j.1365-2141.1998.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute leukaemia in Jehovah's Witnesses

Abstract: Summary. The refusal of Jehovah's Witnesses with leukaemia to accept transfusion provides a major clinical challenge because of the myelosuppressive effects of chemotherapy. Experience in treating five such patients is described. Two patients with acute lymphoblastic leukaemia (ALL) achieved remission following chemotherapy, the first without transfusion support, the second, a minor, receiving transfusion under a court order; the first patient remains in remission 5 years later, whereas the second subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
5
23
0
1
Order By: Relevance
“…The therapeutic outcomes of these studies showed a great variation with a high percentage of death due to treatment-induced anemia or disease relapse [4,14,29]. Successful outcomes of treatment did also occur, but these were dependent on the type of leukemia to be treated and on the degree of treatment-related bone marrow aplasia [4,5,14,19,20,22]. However, all data suggest that severe and long-lasting bone marrow aplasia might not in general counteract the idea of transfusion-free oncological treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic outcomes of these studies showed a great variation with a high percentage of death due to treatment-induced anemia or disease relapse [4,14,29]. Successful outcomes of treatment did also occur, but these were dependent on the type of leukemia to be treated and on the degree of treatment-related bone marrow aplasia [4,5,14,19,20,22]. However, all data suggest that severe and long-lasting bone marrow aplasia might not in general counteract the idea of transfusion-free oncological treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients survive even intensive chemotherapy without transfusions [2,3]. So far, only a few cancer treatments in pediatric patients of Jehovah's Witnesses were described [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports concerning leukemia in Jehovah's Witnesses show that the achievement of remission with a heavy therapy is possible, [1][2][3][4] and this may be curative; however, many ethical implications are raised by investigators, mainly concerning the choice whether to treat or not to treat and, if so, what appropriate therapy is to be performed. Almost all our patients, before the transplant procedure, received a standard therapy, except two patients who received a shortened course of therapy to avoid a long duration of myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, physicians refuse to take care of these patients or they propose less aggressive therapies than expected in these diseases. 1 However, there are several reports emphasizing that the cure of leukemia is possible, also without the support of transfusions, 2-4 but single case reports are very anecdotal and there are no sequential studies reported. Although Jehovah's Witnesses deny blood transfusions, they often accept bone marrow or peripheral blood stem cell support.…”
mentioning
confidence: 99%
“…While treating any patient with acute leukemia involves a balance between treating the disease and avoiding treatment toxicity, this balance becomes much more tenuous for patients who refuse blood products. Recent case studies report success in treating Jehovah's Witness leukemia patients [15][16][17]. Alltrans retinoic acid (ATRA) combined with arsenic trioxide has been used with minimal hematological toxicity for patients with acute promyelocytic leukemia (APML), however, only 10% of adults with acute myeloid leukemia have this FAB subtype [16].…”
mentioning
confidence: 99%